Evaluation of level of awareness among coaches regarding the prevalence of sports-related orofacial trauma in children and their first aid and prevention in Delhi-NCR region - Naresh Sharma; Binita Srivastava; Jyoti Batra; Sangeeta Sharma; Puneet Mohan Khari (Journal of International Clinical Dental Research Organization, 2022)
Aims and Objectives: The objective is to evaluate the awareness of sports-related orofacial injuries among coaches in Delhi-NCR region and to determine the awareness in providing the first aid and prevention of sports-related orofacial injuries. Materials and Methods: One hundred and twenty-five coaches of different sports academies/schools were selected from Delhi-NCR region. The study was explained to all coaches, and written informed consent was taken. A questionnaire consisting of 24 questions was given to them and they were asked to fill that questionnaire on the spot. Awareness of coaches regarding the role of dentist in sports academies or during sports events was evaluated through the questionnaire. All questionnaires filled by the coaches were evaluated with the help of professional statistician. Conclusion: From the study it can be concluded that, the knowledge of coaches regarding prevention and first-aid of orofacial trauma is not satisfactory. This is the major concern regarding their knowledge in dealing with dental injuries.